The Detailed Anatomy of the Deep Plane of the Face and Neck with Current Nomenclature - Talei, Benjamin; Ziai, Hedyeh (Facial Plastic Surgery, 2024)
The fundamental goal of modern face and neck lifting is to enhance and restore a more youthful facial appearance by addressing soft tissue descent. There are variations in described facelift technique including superficial musculoaponeurotic system (SMAS) flaps, composite flaps, deep plane, skin flaps, and subperiosteal facelifts, among others. The term “deep plane rhytidectomy” was originally described by Hamra. This term has since been linked with facelift surgery with recent advances including incision placement, treatments of SMAS–platysma complex, and mastoid crevasse among others. In the lead authors' experience, using deep plane techniques have demonstrated superior facial surgical rejuvenation results with less dependence on ancillary measures such as fat grafting or implantation for midface volumization. In order to successfully perform any face or neck lift, it is key to understand the relationship of the skin, the fat compartments, and the ligamentous attachments. This chapter details the anatomy of the deep plane of the face and neck and explains some nuances as it relates to surgical lifting. We also describe recent anatomical revelations of the mandibular ligament and its management in deep plane face lifting. In this chapter, given this opportunity to share personal experiences and preferences, the authors hope to describe relevant anatomy for the deep plane and provide some clarity on the merits of deep plane face and neck lift technique.
Keywords: deep plane; face lift; neck lift; rhytidectomy; SMAS